Alcune note su Bernardino Barbuleio, grammatico, oratore e committente nella Ferrara del XVI secolo - Chiara Sturaro (Annali Online dell'Università di Ferrara. Sezione Lettere)
The presence of the monumental sarcophagus of Bernardino Barbuleio at Palazzo Renata di Francia, that houses the University of Ferrara and its Lapidary, suggested a research on the owner of the marble tomb, a scholar and canon who lived between the 15th and the 16th century in the city of the Este Family. Analyzing the records of some of the most important professors affiliated to the University of Ferrara at that time and the accounts of Barbuleio’s initiatives as the pastor of the important church of San Pietro (a subsidiary of the Cathedral of San Giorgio fuori le mura), this paper sheds light on the figure of Bernardino Barbuleio, recognizing his role as a competent and erudite preceptor in Ferrara and an active priest who commissioned some works to the famous painter Garofalo.